PEGylation of the antimicrobial peptide LyeTx I-b maintains structure-related biological properties and improves selectivity - Moreira Brito, Júlio César; Carvalho, Lucas Raposo; Neves de Souza, Amanda; Carneiro, Guilherme; Magalhães, Paula Prazeres; Farias, Luiz Macêdo; Guimarães, Natália Rocha; Verly, Rodrigo Moreira; Resende, Jarbas Magalhães; Elena de Lima, Maria (Frontiers in Molecular Biosciences, 2022)
The biological activity of antimicrobial peptides and proteins is related to their structural aspects and is sensible to post-translational modifications like PEGylation. However, PEGylation of protein and peptide drugs has expanded in recent years due to the reduction of their toxicity. Due to their size, PEGylation can preserve or compromise the overall structure of these biopolymers and, thus biological properties. LyeTx I-bcys was synthesized by Fmoc strategy and coupled to polyethylene glycol 2.0 kDa. The conjugates were purified by HPLC and characterized by MALDI-ToF-MS analysis. Microbiological assays with LyeTx I-bcys and LyeTx I-bPEG were performed against Staphylococcus aureus (ATCC 33591) and Escherichia coli (ATCC 25922) in liquid medium. MIC values of 2.0 and 1.0 µM for LyeTx I-bcys and 8.0 and 4.0 µM for LyeTx I-bPEG were observed against S. aureus and E. coli, respectively. PEGylation of LyeTx I-bcys (LyeTx I-bPEG) decreased the cytotoxicity determined by MTT method for VERO cells compared to the non-PEGylated peptide. In addition, structural and biophysical studies were performed to evaluate the effects of PEGylation on the nature of peptide-membrane interactions. Surface Plasmon Resonance experiments showed that LyeTx I-b binds to anionic membranes with an association constant twice higher than the PEGylated form. The three-dimensional NMR structures of LyeTx I-bcys and LyeTx I-bPEG were determined and compared with the LyeTx I-b structure, and the hydrodynamic diameter and zeta potential of POPC:POPG vesicles were similar upon the addition of both peptides. The mPEG-MAL conjugation of LyeTx I-bcys gave epimers, and it, together with LyeTx I-bPEG, showed clear α-helical profiles. While LyeTx I-bcys showed no significant change in amphipathicity compared to LyeTx I-b, LyeTx I-bPEG was found to have a slightly less clear separation between hydrophilic and hydrophobic faces. However, the similar conformational freedom of LyeTx I-b and LyeTx I-bPEG suggests that PEGylation does not cause significant structural changes. Overall, our structural and biophysical studies indicate that the PEGylation does not alter the mode of peptide interaction and maintains antimicrobial activity while minimizing tissue toxicity, which confirmed previous results obtained in vivo. Interestingly, significantly improved proteolytic resistance to trypsin and proteinase K was observed after PEGylation.